2012
DOI: 10.1055/s-0032-1305282
|View full text |Cite
|
Sign up to set email alerts
|

Einflüsse medizinischer Aufklärungsarbeit auf Erste-Hilfe- und AED-Kenntnisse in der Allgemeinbevölkerung

Abstract: The placement of AED on public places in combination with an intensive medical education results in a high acceptance and recognition of AED. Nevertheless, following our date it seems to be doubtful that this results automatically in a higher attendance to acquire knowledge in first-aid and AED use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(26 reference statements)
1
4
0
2
Order By: Relevance
“…This shows how small public awareness is of the mentioned devices. Similar conclusions were reached in the surveys by Christ et al [15]. AEDs, as well as mobile applications, are programmed to help the rescuer follow the CPR + AED algorithm.…”
Section: Discussionsupporting
confidence: 74%
“…This shows how small public awareness is of the mentioned devices. Similar conclusions were reached in the surveys by Christ et al [15]. AEDs, as well as mobile applications, are programmed to help the rescuer follow the CPR + AED algorithm.…”
Section: Discussionsupporting
confidence: 74%
“…The lack of knowledge among members of the public regarding AED use was a key finding of this review. This was particularly evident in the studies of Schober et al, 29 Bogle et al, 26 Christ et al, 24 and Taniguchi et al 27 Schober et al 29 found that only a minority of individuals had sufficient knowledge and would be willing to use an AED. Only 61 of the 1018 train passengers surveyed spontaneously indicated that they would consider AED use when confronted with a SCA.…”
Section: Discussionmentioning
confidence: 95%
“…A medical official with extensive background in SCA emergency response and research recommended one further article for consideration. 24 The flowchart of the study selection results is presented below in Figure 2.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Schwierigkeit besteht darin, die Bevölkerung hierzu zu motivieren[4]. Vielleicht kann die Motivation der Laien in Deutschland jedoch dadurch gesteigert werden, dass ihnen vermittelt wird, dass ihre Erste-Hilfe-Kenntnisse und dabei insbesondere die Kenntnisse in der Reanimation, am ehesten den eigenen (Ehe-)Partner, Verwandte und Freunde vor dem plötzlichen Herztod schützen und erst an letzter Stelle unbekannte Fremde.Möglicherweise werden die Ergebnisse unserer Studie dadurch beeinflusst, dass wir lediglich diejenigen außerklinischen HerzKreislauf-Stillstände untersuchen konnten, die in unsere Klinik gebracht wurden.…”
unclassified